2008
DOI: 10.1093/scan/nsn020
|View full text |Cite
|
Sign up to set email alerts
|

Self-reflection across time: cortical midline structures differentiate between present and past selves

Abstract: The processing of personal changes across time and the ability to differentiate between representations of present and past selves are crucial for developing a mature sense of identity. In this study, we explored the neural correlates of self-reflection across time using functional magnetic resonance imaging (fMRI). College undergraduates were asked to reflect on their own psychological characteristics and those of an intimate other, for both the present time period (i.e. at college) and a past time period (i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
113
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(127 citation statements)
references
References 46 publications
14
113
0
Order By: Relevance
“…They found that the same MPFC region previously identified as more activated when thinking about the self versus a nonclose other was also more activated when thinking about the self versus an intimate other. Similar results have been obtained in most reports, 15,29,30 although some studies failed to detect differential activity in the MPFC when contrasting judgments referring to the self with judgments referring to a close other. 31,32 The reasons for these divergent findings remain unclear but a possible explanation would be that the difference in MPFC activity when contrasting self and close other conditions depends on the perceived similarity or overlap between oneself and close others, which in turn varies across individuals and situations.…”
Section: Representing One's Personal Characteristics: Semantic Forms supporting
confidence: 89%
See 3 more Smart Citations
“…They found that the same MPFC region previously identified as more activated when thinking about the self versus a nonclose other was also more activated when thinking about the self versus an intimate other. Similar results have been obtained in most reports, 15,29,30 although some studies failed to detect differential activity in the MPFC when contrasting judgments referring to the self with judgments referring to a close other. 31,32 The reasons for these divergent findings remain unclear but a possible explanation would be that the difference in MPFC activity when contrasting self and close other conditions depends on the perceived similarity or overlap between oneself and close others, which in turn varies across individuals and situations.…”
Section: Representing One's Personal Characteristics: Semantic Forms supporting
confidence: 89%
“…White circles represent the locations of peak MPFC activations detected when reflecting on one's own psychological traits relative to reflecting on the traits of others or making semantic judgements. [13][14][15][16][17][18][19][20][21][22][23]25,26,29,30 White squares represent the locations of peak MPFC activations detected when reflecting on one's own promotion goals. [38][39][40][41] when participants made judgments from their own perspective and when they made judgments from the perspective of their friend.…”
Section: Representing One's Personal Characteristics: Semantic Forms mentioning
confidence: 99%
See 2 more Smart Citations
“…Both VMPFC and precuneus are implicated in representations of the self-including [63] autobiographical memory [82] and self-reflexive imagery [14]. VMPFC is particularly recruited in tasks requiring access to affectively relevant information about the self, including personal traits judgments [21,43,84], introspection on one's own feelings [44,46,52,69] and retrieval of emotional information from either past or prospective memory [20,91]. This region is also activated in response to incidental information related to the self without explicit task demands or conscious will [58].…”
Section: Empirical Investigations Of Motor Conversion Disordersmentioning
confidence: 99%